Islam in Diaspora: Shari’a Law, Piety and Brotherhood at al-Farooq Mosque, Atlanta - Mohamad Abdun Nasir (Al-Jami'ah Research Centre, 2016)
This article examines Islamic ritual performance of Eid prayer amongst Muslims in Diaspora at al-Farooq Mosque in Atlanta, the US, whose congregational members come from all around the world. Using textual and ethnographical methods, this study focuses on the implementation of shari’a law concerning Islamic prayer and on the meaning and experience of the ritual that emerge amongst the participants who perform it. This study demonstrates that the Eid ritual performance has created a special meaning and particular experience. The ritual is seen as the medium through which the performers forge their piety and strengthen the spirit of brotherhood. The ritual strengthens the brotherhood of the performers, who hold different ethnical and cultural backgrounds. However, the core ritual of Eid prayer remains Islamic and is built on the Muslim Hanafi School. Shari’a law concerning prayer is upheld to maintain the basic requirement where every ritual must be based on the sound Islamic texts. This suggests that the context, namely diasporic Muslim in America, has (re)shaped the meaning of the ritual but does not change the core of the ritual practice.[Tulisan ini mengkaji praktik ritual shalat hari raya (Eid) di masjid al-Farooq Atlanta, Amerika Serikat pada kalangan muslim perantauan dari berbagai belahan dunia. Kajian ini, dengan menggunakan pendekatan tektual dan etnografi, mengamati penerapan hukum Islam dalam hal peribadatan dan pemaknaan serta pengalaman ritual diantara mereka. Studi ini menunjukkan bahwa shalat hari raya memberi makna dan pengalaman khusus. Perayaan ini dilihat sebagai medium untuk menunjukkan kesalehan dan menguatkan ikatan persaudaraan sesama muslim meskipun mempunyai latar belakang etnik dan budaya yang berbeda. Meskipun demikian, inti dari ritual tersebut menunjukkan aliran mazhab Hanafi. Pelaksanaan fiqih dalam sholat Eid tetap berpegang pada Qur’an dan Hadits. Dengan kata lain, konteks geografi dan budaya yang berbeda telah membentuk makna baru namun tetap tidak merubah inti dari praktik ibadah yang bermazhab Hanafi.]